Characteristics of graphite obtained by recycling lithium - iron phosphate batteries - Іvan Shcherbatiuk; Hanna Potapenko; Danylo Panchenko; Volodymyr Khomenko; Dmytro Patlun; Borys Halyuk; Roman Derkach; Olexander Potapenko; Viacheslav Barsukov (Journal of Electrochemical Science and Engineering, 2024)
Based on both the economic and environmental points of view, processing used lithium-ion batteries (LIBs) is of great importance. The valuable components contained in LIB (cathode, anode and current collectors) generate high interest in solving the problem of resource deficiency and reducing environmental destruction due to overexploitation. The starting anode material extracted from a used lithium iron phosphate battery is a mixture of graphite, acetylene carbon black, and polymer binder. Reusing this material in lithium batteries without additional cleaning is impractical owing to poor electrochemical characteristics and the presence of impurities. To achieve effective regeneration, the recycled anode material is first treated in a nitric acid solution to remove copper foil and lithium ions with electrolyte interaction products formed during battery operation. The next step is heat treatment of the material, which allows the removal of acetylene soot and polymer glue binder. The tests showed sufficiently high values of the specific capacity of recycled graphite (~330 mA h g-1 at 0.1 C), which are comparable to commercial materials and meet the requirements of reuse.